ASESMEN PROKRASTINASI AKADEMIK BERBASIS COMPUTER ASSISTED TESTING (CAT) - Rihya Syifa Qurrotu Ayuna; Herdi Herdi (Jurnal Mahasiswa BK An-Nur : Berbeda, Bermakna, Mulia, 2023)
Information technology-based Bk assessment is a process of collecting, processing, analyzing, interpreting and reporting data or information by utilizing information and communication technology. Information and communication technology is able to facilitate and improve all assessment practices in schools. So that it can help improve the results of the validity and reliability of test results as well as provide an efficient and valid assessment of counseling alliances.This study uses a development model (Research and Development) with a procedural model that is descriptive describing the steps to produce a product. The product referred to in this development is the Computer Assisted Test (CAT) program on academic procrastination assessment. The applications that we will introduce are Google forms, Quizizz and Kahoot. the application of research and development is carried out through three stages; 1). Mode Pre-Development Stage, 2). Model development stage and 3). Model Implementation Stage.The results of the study show that the Computer Assisted Testing (CAT) based assessment is more optimal than the implementation of manual tests using paper. Because CAT is able to display dynamic and interactive visuals, icons, animations, and sounds. The score results can be directly seen by students and the counseling teacher can directly import the assessment results data from the platform used into the data storage system